Effect of Sugar Substitution with Date Extract and Honey on the Characteristics of Ginger Hard Candy - Sakdiyah, Anis Fatus; Cahyaning Rini Utami (Jurnal Pangan dan Agroindustri, 2025)
Ginger hard candy is a functional food combining the health benefits of ginger with sweetness. This study examined the substitution of granulated sugar and glucose with date extract (Phoenix dactylifera L.) and honey (Apis mellifera) on the physical, chemical, and sensory characteristics of ginger hard candy. A Completely Randomized Design with five substitution levels (0–100%) and three replications was used. Data were statistically analyzed, and the best treatment was selected using the Effectiveness Index method. Substitution significantly influenced most parameters except color. P1 (100% sugar) showed the highest physical and sensory quality (moisture 0.57%, aw 0.49, reducing sugar 0.13%, antioxidant activity 29.69%), whereas P3 (50% date extract and honey) provided balanced sensory acceptance with markedly higher antioxidant activity (62.26%) and acceptable moisture (1.45%), water activity (0.51), and reducing sugar (0.37%), all complying with SNI and FDA standards. Further study on cooking conditions, packaging, and stability is recommended.